Do nitric oxide synthase and cyclooxygenase contribute to sweating response during passive heating in endurance‐trained athletes?. Issue 17 (12th September 2017) - Amano, Tatsuro; Fujii, Naoto; Kenny, Glen P.; Inoue, Yoshimitsu; Kondo, Narihiko
Abstract: The aim of our study was to determine if habitual endurance training can influence the relative contribution of nitric oxide synthase (NOS) and cyclooxygenase (COX) in the regulation of sweating during a passive heat stress in young adults. Ten trained athletes and nine untrained counterparts were passively heated until oral temperature (as estimated by sublingual temperature, Tor ) increased by 1.5°C above baseline resting. Forearm sweat rate (ventilated capsule) was measured at three skin sites continuously perfused with either lactated Ringer's solution (Control), 10 mmol/L N G ‐nitro‐L ‐arginine methyl ester (L ‐NAME, non‐selective NOS inhibitor), or 10 mmol/L ketorolac (Ketorolac, non‐selective COX inhibitor) via intradermal microdialysis. Sweat rate was averaged for each 0.3°C increase in Tor . Sweat rate at theL ‐NAME site was lower than Control following a 0.9 and 1.2°C increase in Tor in both groups (all P  ≤   0.05). Relative to the Control site, NOS‐inhibition reduced sweating similarly between the groups ( P  =   0.51). Sweat rate at the Ketorolac site was not different from the Control at any levels of Tor in both groups ( P  >   0.05). Nevertheless, a greater sweat rate was measured at the end of heating in the trained as compared to the untrained individuals ( P  ≤   0.05). We show that NOS contributes similarly to sweating in both trained and untrained individuals during a passive heat stress. Further, no effect of COX on sweating was measured for either group. The greater sweat production observed in endurance‐trained athletes is likely mediated by factors other than NOS‐ and COX‐dependent mechanisms. Abstract : We compared the relative contribution of nitric oxide synthase (NOS) and cyclooxygenase (COX) in the regulation of sweating in endurance trained and untrained young adults during a passive heating. We show that NOS contributes similarly to sweating in both trained and untrained individuals while no effect of COX on sweating was measured for either group during passive heating. The greater sweat production observed in endurance‐trained athletes is likely mediated by factors other than NOS‐ and COX‐dependent mechanisms.